Determination of Nuclear Track Parameters for LR - 115 Detector by Using of MATLAB Software Technique - Al - Jomaily, Firas M; Al - jobouri, Hussain A; Mheemeed, Ahmed K (Al-Nahrain Journal of Science, 2018)
The nuclear track detector parameters, such as nuclear track diameter D(μm ), number of track NT and area of track AT were determined by using MATLAB software technique for IR-115 detector irradiated by alpha particle from 241Am source under 1.5, 2.5 and 3.5 Mev at etching time TB of 90, 120, 150 and 180 min. By using the image analysis of MATLAB software for nuclear track, the full width at half maximum FWHM and relative resolution R% were calculated for each energy of alpha particles. In this study, it was shown that increasing the alpha energy on the IR-115 detector leads to increased in etching time TB and the dropping of R% to minimum value, and then reach a stable value before dropping at values 1.5, 2.5 Mev and unstable at 3.5 Mev. Imaging analysis by MATLAB technique which used in this study reflect good and accurate results for nuclear track detector parameters and we recommend using this technique for the determination of these parameters.